Experimental dimensions and precision in trials with millet and slender leaf rattlebox - Cargnelutti Filho, Alberto; Neu, Ismael; Loregian, Marcos; Bubans, Valéria; Somavilla, Felipe; Dumke, Gabriel (Revista Ciência Agronômica, 2021)
The objective of this study was to determine the optimal plot size to evaluate fresh matter in millet (Pennisetum glaucum L.) and slender leaf rattlebox (Crotalaria ochroleuca), in scenarios formed by combinations of numbers of treatments, numbers of replicates, and levels of precision. Fifteen uniformity trials with millet and slender leaf rattlebox, in single cropping or intercropping, were carried out. Fresh matter was evaluated in 540 basic experimental units (BEU) of 1 m × 1 m (15 trials × 36 BEU per trial). The soil heterogeneity index of Smith (1938) was estimated. Plot size was determined by the method of Hatheway (1961) in scenarios formed by combinations of i treatments (i = 5, 10, 15 and 20), r replicates (r = 3, 4, 5, 6, 7 and 8), and d precision levels (d = 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18% and 20%). To evaluate the fresh matter of millet and slender leaf rattlebox, in single or intercropping, in experiments in completely randomized or randomized block designs, with 5 to 20 treatments and with five replicates, plots with 10 m² of usable area are sufficient for differences between treatments of 10% of the overall mean of the experiment to be considered significant at 0.05 probability level.